2005
DOI: 10.1007/s00425-005-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid and stress treatment are essential for the acquisition of embryogenic competence by carrot somatic cells

Abstract: Studies of carrot embryogenesis have suggested that abscisic acid (ABA) is involved in somatic embryogenesis. A relationship between endogenous ABA and the induction of somatic embryogenesis was demonstrated using stress-induced system of somatic embryos. The embryonic-specific genes C-ABI3 and embryogenic cell proteins (ECPs) were expressed during stress treatment prior to the formation of somatic embryos. The stress-induction system for embryogenesis was clearly distinguished by two phases: the acquisition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 42 publications
3
59
1
4
Order By: Relevance
“…Sucrose treatment leads the explants to an inactive state, although it can still induce embryogenesis. Our previous study revealed that various stress treatments induce embryogenesis (Kikuchi et al 2006). The study also showed that the response of stress-treated explants is relatively slow.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Sucrose treatment leads the explants to an inactive state, although it can still induce embryogenesis. Our previous study revealed that various stress treatments induce embryogenesis (Kikuchi et al 2006). The study also showed that the response of stress-treated explants is relatively slow.…”
Section: Discussionmentioning
confidence: 91%
“…For this reason, it has been postulated that embryogenic cells are already programmed for early-and late-stage embryogenesis at the molecular level, and it is difficult to efficiently isolate early embryonic genes using these cells (Kiyosue et al 1991(Kiyosue et al , 1993a(Kiyosue et al , 1993b. However, in the stress-induction system, the induction of embryonic gene expression corresponds to the acquisition of embryogenic competence during stress (Kikuchi et al 2006). The expression levels of early embryonic genes are thought to be enhanced under conditions of stress, and comparing expression profiles using the stress-induction system can help in isolating these genes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations